Metastatic adenocarcinoma to the brain - Carrier, D.A. (1994)
PURPOSE To describe the appearance on T2-weighted scans of metastatic adenocarcinoma to the brain and to show that the hypointensity frequently associated with these lesions is not related to the presence of mucin, blood products, iron, or calcium. METHODS The MR scans of 14 patients with metastatic adenocarcinoma to the brain were reviewed retrospectively. The signal intensity on T2-weighted scans of the solid enhancing portion of the tumors was compared with white matter. Histologic examination of the surgical specimens included special stains to search for calcium, mucin, and iron. RESULTS Eight of nine surgical and all six nonsurgical lesions were either iso- or hypointense to white matter on T2-weighted scans. There was no correlation with tumor histology or the presence of mucin, blood products, iron, or calcium. CONCLUSIONS The presence of a hypointense intraaxial mass on T2-weighted scans strongly suggests the possibility of metastatic adenocarcinoma. The MR appearance is not explained by the presence of mucin, blood products, iron, or calcium. This phenomenon most likely reflects the relaxation parameters of the tissue from which the metastasis arose.